Subgingival microbiota and periodontal clinical status in patients with plaque psoriasis: A cross-sectional study - Grissel Orozco-Molina; Miguel Casillas-Santana; Abigailt Flores-Ledesma; Fernando Martínez-Arroniz; Eduardo Castañeda-Saucedo; Víctor Martínez-Aguilar; Andrés Diaz-Zuñiga; Gladys León-Dorantes; Juan Antonio Arreguin-Cano (Indian Journal of Dermatology, 2023)
Plaque Psoriasis (PP) and periodontitis are inflammatory disorders with a bidirectional association. They both have a qualitatively similar immune-modulatory cascade, cytokine profile, and a recently described dysbiosis. Different oral bacterial species compositions in the periodontal pocket might play a role in the development of PP. To describe the subgingival microbiota of the Mexican population with PP and the periodontal conditions. Subjects were divided into two groups: periodontal health (PH) (PH-non-PP, PH-PP) and periodontitis (PD) (P-non-PP, PD-PP). Following clinical examination, the patients were classified into three groups according to the degree of psoriasis as measured by the Psoriasis Area Severity Index (PASI) and the periodontal status according to the parameters of the American Academy of Periodontology (AAP). Subgingival microbiota samples of each patient were used to determine 40 species of periodontal bacteria by checkerboard DNA-DNA hybridization. IL-2 and IL-6 were measured by ELISA. Of the forty-eight patients with PP, 21 patients had PH and 27 patients had PD. PD-PP group has a significant increase in the percentage of plaque, gingival redness, pocket probing depth, and clinical attachment loss (P<0.001) compared to PH-PP group. Microbiologically PD-PP exhibited significantly higher mean counts for A. georgiae, A. israelii, A. naeslundii from blue complex (P<0.001) than PD-non-PP. Moreover, the counts of these Actinomyces in PD-PP increased according to the severity of index PASI. The concentration of IL-2 and IL-6 were increased in saliva from PH-PP and PD-PP patients compared to PH non-PP. PP individuals harbored a particular sub-gingival microbiota profile different from non-PP. The severity of psoriasis was related to dysbiosis of microbiota —PASI > 5 related to periodontitis with the predominance of Actinomyces periodontal, irrespective of their periodontal condition. Finally, the severity of psoriasis could be unbalanced in subgingival microbiota and increase the risk to develop periodontitis.